2015
DOI: 10.1002/acr.22574
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Use in Patients With Systemic Lupus Erythematosus: Association Between Dose and Health Care Utilization and Costs

Abstract: Objective. To investigate the determinants of health care utilization and costs with use of glucocorticoid (GC) drugs among adult systemic lupus erythematosus (SLE) patients. Methods. This cross-sectional study analyzed established SLE patients identified by International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes from a large US insurance claims database in 2007-2011. Five patient groups were defined by their oral GC use during a 1-year period: non-GC users, <60 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 25 publications
(29 reference statements)
5
63
1
Order By: Relevance
“…While the literature is more limited concerning the impact of corticosteroid use on healthcare costs in the RA population, similar findings have been noted in studies of corticosteroid use in other chronic autoimmune disease populations. For example, a study by Chen et al among patients with systemic lupus erythematosus found that glucocorticoid users compared to non-users had significantly greater healthcare utilization and costs [34]. Although our findings suggest that RA patients who use corticosteroids incur greater healthcare utilization and costs than those who do not, the reasons for this pattern are not known.…”
Section: Discussioncontrasting
confidence: 74%
“…While the literature is more limited concerning the impact of corticosteroid use on healthcare costs in the RA population, similar findings have been noted in studies of corticosteroid use in other chronic autoimmune disease populations. For example, a study by Chen et al among patients with systemic lupus erythematosus found that glucocorticoid users compared to non-users had significantly greater healthcare utilization and costs [34]. Although our findings suggest that RA patients who use corticosteroids incur greater healthcare utilization and costs than those who do not, the reasons for this pattern are not known.…”
Section: Discussioncontrasting
confidence: 74%
“…Following the title/abstract and full-text reviews, data from 32 articles were extracted. 3,4,9,11,13, This count of articles was proportionally similar to those identified by Manson et al, 3 given the difference in the time periods considered. Figure 3 and Table II summarize the characteristics of the 32 articles extracted.…”
Section: Summary Statisticssupporting
confidence: 73%
“…The median time to first damage of the whole cohort was 3 years, with almost 20% of patients accruing damage within the first year; similar numbers have recently been reported by the SLICC group . Therefore, damage prevention should be a priority from the very first visit , since it has been demonstrated that damage causes further damage, deteriorates quality of life, and increases the costs of patients’ care .…”
Section: Discussionsupporting
confidence: 61%